CORRECTIVE EFFECT OF PHYSICAL LOADS USED AT DIFFERENT TIMES OF THE DAY IN METABOLIC DISORDERS (EXPERIMENTAL STUDY) - Milovanova K.G.; Orlova A.A.; Kollantay O.V.; Shuvalov I.Yu. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the effect of physical activity used at different times of the day on metabolic disorders in an experiment on mice with a model of type II diabetes mellitus. Methods and structure of the study. The effect of physical activity used at different times of the day on metabolic disorders was studied in an experiment on mice with a model of type II diabetes mellitus. Results and conclusions. It has been shown that forced physical activity in the form of daily treadmill running has a number of pronounced effects on the metabolism in mice with type II diabetes mellitus. This is manifested in a decrease in body weight, an increase in the rate of glucose uptake. All of the above indicates the normalization of carbohydrate metabolism under the influence of regular physical activity and the involution of changes characteristic of type II diabetes mellitus. It is also important that the physical effects depend on the time of day. A greater effect is the use of activity during the period of the day when the animals are passive (daylight hours), as well as shift training. The results obtained reveal a promising way of influencing metabolic processes, which is very important for finding new ways to correct metabolic disorders in type II diabetes mellitus.